Neutrophils Do Not Express IL-17A in the Context of Acute Oropharyngeal Candidiasis - Huppler, Anna R. (Pathogens, 2015)
IL-17 protects against pathogens by acting on nonhematopoietic cells to induce neutrophil recruitment through upregulation of chemokines and G-CSF. IL-17- and Th17-deficient humans and mice are susceptible to mucosal Candida albicans infections, linked to impaired neutrophil responses. IL-17 production is traditionally associated with CD4(+) Th17 cells. However, IL-17 is also expressed during innate responses to facilitate rapid pathogen clearance. Innate IL-17-expressing cells include various lymphocyte-type subsets, including ILC3, NKT, γδ-T and “natural” Th17 (nTh17) cells. Some reports suggest that neutrophils can express IL-17 during fungal infections. Here, we asked whether neutrophils serve as a source of IL-17 during acute oropharyngeal candidiasis (OPC) using an IL-17A fate-tracking reporter mouse. Mice were subjected to OPC for two days, and oral tissue was analyzed by flow cytometry. IL-17A was expressed by γδ-T cells and TCRβ(+) natural Th17 (nTh17) cells, as recently reported. Although infiltrating neutrophils were recruited to the tongue following infection, they did not express the IL-17A reporter. Moreover, neutrophil-depleted mice exhibited normal transcription of both Il17a and downstream IL-17-dependent gene targets after Candida challenge. Thus, in acute OPC, neutrophils are not a measurable source of IL-17 production, nor are they necessary to trigger IL-17-dependent gene expression, although they are essential for ultimate pathogen control.